KERAPATAN STOMATA DAN KAITANNYA TERHADAP KEKERINGAN PADA TANAMAN PADI VARIETAS IR64 - Rahabistara Sumadji, Angga (Widya Warta, 2020)
Stomata plays an important role as a tool for plant adaptation to drought stress. Rice plants adapt to drought stress by reducing the size of the stomata and the number of stomata. This study  aims  to  determine  the  relationship  between  stomata  density  and  drought  resistancein IR64  rice    variety.  The  research  method  is  conducted  by  observing  stomata  varieties  of  IR64 rice  which  was  treated  with  drought  stress  treatment.  The  results  of  the  research  show  that IR64 rice variety has a better level of resistance to drought because IR64 rice variety has low stomata density and stomata index.